Variation of syllepsis in eleven tamarack [Larix laricina (Du Roi) K. Koch] provenances in Northwestern Ontario and its relation with height growth - Shaotang, Deng (My University, 1990)
Variation in syllepsis of tamarack and its relationship to juvenile height growth in eleven tamarack provenances from northwestern Ontario was evaluated in a four-year-old clonal test planted at Thunder Bay, Ontario. Significant provenance and clone-within-provenance effects were found for height growth, and occurrence and degree of syllepsis. There existed a south-north trend of decreasing provenance means for both height growth and degree of syllepsis. Degree of syllepsis was found to be moderately correlated with current-year height growth. Provenance broad-sense heritability estimates ranged from 0.22 to 0.23 for 1989 final height and 1989 height growth respectively, and they ranged from 0.11 to 0.13 for number and length of sylleptic branches on 1989 height growth. Clonal broad-sense heritability estimates ranged from 0.16 to 0.18 for 1989 final height and 1989 height growth respectively, and they ranged from 0.33 to 0.37 for number and length of sylleptic branches on 1989 height growth. Although syllepsis of tamarack has high phenotypic plasticity, the potential for its development on tamarack is heritable. Syllepsis of tamarack may be an evolutionary mechanism that permits tamarack trees to deal with environmental uncertainty.
Keywords: Tamarack Variation; Tamarack Growth; Shoots (Botany); Broad-sense heritability; Genetic correlation & variation; Sylleptic long shoot